lean2/src/builtin/kernel.lean

1039 lines
44 KiB
Text
Raw Normal View History

-- Copyright (c) 2014 Microsoft Corporation. All rights reserved.
-- Released under Apache 2.0 license as described in the file LICENSE.
-- Author: Leonardo de Moura
import macros
import tactic
universe U ≥ 1
definition TypeU := (Type U)
-- create default rewrite rule set
(* mk_rewrite_rule_set() *)
variable Bool : Type
-- Reflexivity for heterogeneous equality
-- We use universe U+1 in heterogeneous equality axioms because we want to be able
-- to state the equality between A and B of (Type U)
axiom hrefl {A : (Type U+1)} (a : A) : a == a
-- Homogeneous equality
definition eq {A : (Type U)} (a b : A) := a == b
infix 50 = : eq
theorem refl {A : (Type U)} (a : A) : a = a
:= hrefl a
theorem heq_eq {A : (Type U)} (a b : A) : (a == b) = (a = b)
:= refl (a == b)
definition true : Bool
:= (λ x : Bool, x) = (λ x : Bool, x)
theorem trivial : true
:= refl (λ x : Bool, x)
set_opaque true true
definition false : Bool
:= ∀ x : Bool, x
set_opaque false true
alias : true
alias ⊥ : false
definition not (a : Bool) := a → false
notation 40 ¬ _ : not
definition or (a b : Bool) := ¬ a → b
infixr 30 || : or
infixr 30 \/ : or
infixr 30 : or
definition and (a b : Bool) := ¬ (a → ¬ b)
infixr 35 && : and
infixr 35 /\ : and
infixr 35 ∧ : and
definition implies (a b : Bool) := a → b
definition neq {A : (Type U)} (a b : A) := ¬ (a = b)
infix 50 ≠ : neq
theorem a_neq_a_elim {A : (Type U)} {a : A} (H : a ≠ a) : false
:= H (refl a)
definition iff (a b : Bool) := a = b
infixr 25 <-> : iff
infixr 25 ↔ : iff
theorem em (a : Bool) : a ¬ a
:= assume Hna : ¬ a, Hna
theorem not_intro {a : Bool} (H : a → false) : ¬ a
:= H
theorem absurd {a : Bool} (H1 : a) (H2 : ¬ a) : false
:= H2 H1
-- The Lean parser has special treatment for the constant exists.
-- It allows us to write
-- exists x y : A, P x y and ∃ x y : A, P x y
-- as syntax sugar for
-- exists A (fun x : A, exists A (fun y : A, P x y))
-- That is, it treats the exists as an extra binder such as fun and forall.
-- It also provides an alias (Exists) that should be used when we
-- want to treat exists as a constant.
definition Exists (A : (Type U)) (P : A → Bool)
:= ¬ (∀ x, ¬ (P x))
definition exists_unique {A : (Type U)} (p : A → Bool)
:= ∃ x, p x ∧ ∀ y, y ≠ x → ¬ p y
axiom case (P : Bool → Bool) (H1 : P true) (H2 : P false) (a : Bool) : P a
theorem false_elim (a : Bool) (H : false) : a
:= case (λ x, x) trivial H a
theorem mt {a b : Bool} (H1 : a → b) (H2 : ¬ b) : ¬ a
:= assume Ha : a, absurd (H1 Ha) H2
theorem contrapos {a b : Bool} (H : a → b) : ¬ b → ¬ a
:= assume Hnb : ¬ b, mt H Hnb
theorem absurd_elim {a : Bool} (b : Bool) (H1 : a) (H2 : ¬ a) : b
:= false_elim b (absurd H1 H2)
-- Recall that or is defined as ¬ a → b
theorem or_introl {a : Bool} (H : a) (b : Bool) : a b
:= assume H1 : ¬ a, absurd_elim b H H1
theorem or_intror {b : Bool} (a : Bool) (H : b) : a b
:= assume H1 : ¬ a, H
theorem boolcomplete (a : Bool) : a = true a = false
:= case (λ x, x = true x = false)
(or_introl (refl true) (true = false))
(or_intror (false = true) (refl false))
a
theorem boolcomplete_swapped (a : Bool) : a = false a = true
:= case (λ x, x = false x = true)
(or_intror (true = false) (refl true))
(or_introl (refl false) (false = true))
a
theorem resolve1 {a b : Bool} (H1 : a b) (H2 : ¬ a) : b
:= H1 H2
axiom subst {A : (Type U)} {a b : A} {P : A → Bool} (H1 : P a) (H2 : a = b) : P b
-- Alias for subst where we provide P explicitly, but keep A,a,b implicit
theorem substp {A : (Type U)} {a b : A} (P : A → Bool) (H1 : P a) (H2 : a = b) : P b
:= subst H1 H2
theorem symm {A : (Type U)} {a b : A} (H : a = b) : b = a
:= subst (refl a) H
theorem trans {A : (Type U)} {a b c : A} (H1 : a = b) (H2 : b = c) : a = c
:= subst H1 H2
theorem congr1 {A B : (Type U)} {f g : A → B} (a : A) (H : f = g) : f a = g a
:= substp (fun h : A → B, f a = h a) (refl (f a)) H
theorem congr2 {A B : (Type U)} {a b : A} (f : A → B) (H : a = b) : f a = f b
:= substp (fun x : A, f a = f x) (refl (f a)) H
theorem congr {A B : (Type U)} {f g : A → B} {a b : A} (H1 : f = g) (H2 : a = b) : f a = g b
:= subst (congr2 f H2) (congr1 b H1)
theorem true_ne_false : ¬ true = false
:= assume H : true = false,
subst trivial H
theorem absurd_not_true (H : ¬ true) : false
:= absurd trivial H
theorem not_false_trivial : ¬ false
:= assume H : false, H
-- "equality modus pones"
theorem eqmp {a b : Bool} (H1 : a = b) (H2 : a) : b
:= subst H2 H1
infixl 100 <| : eqmp
infixl 100 ◂ : eqmp
theorem eqmpr {a b : Bool} (H1 : a = b) (H2 : b) : a
:= (symm H1) ◂ H2
theorem imp_trans {a b c : Bool} (H1 : a → b) (H2 : b → c) : a → c
:= assume Ha, H2 (H1 Ha)
theorem imp_eq_trans {a b c : Bool} (H1 : a → b) (H2 : b = c) : a → c
:= assume Ha, H2 ◂ (H1 Ha)
theorem eq_imp_trans {a b c : Bool} (H1 : a = b) (H2 : b → c) : a → c
:= assume Ha, H2 (H1 ◂ Ha)
theorem to_eq {A : (Type U)} {a b : A} (H : a == b) : a = b
:= (heq_eq a b) ◂ H
theorem to_heq {A : (Type U)} {a b : A} (H : a = b) : a == b
:= (symm (heq_eq a b)) ◂ H
theorem iff_eliml {a b : Bool} (H : a ↔ b) : a → b
:= (λ Ha : a, eqmp H Ha)
theorem iff_elimr {a b : Bool} (H : a ↔ b) : b → a
:= (λ Hb : b, eqmpr H Hb)
theorem ne_symm {A : (Type U)} {a b : A} (H : a ≠ b) : b ≠ a
:= assume H1 : b = a, H (symm H1)
theorem eq_ne_trans {A : (Type U)} {a b c : A} (H1 : a = b) (H2 : b ≠ c) : a ≠ c
:= subst H2 (symm H1)
theorem ne_eq_trans {A : (Type U)} {a b c : A} (H1 : a ≠ b) (H2 : b = c) : a ≠ c
:= subst H1 H2
theorem eqt_elim {a : Bool} (H : a = true) : a
:= (symm H) ◂ trivial
theorem eqf_elim {a : Bool} (H : a = false) : ¬ a
:= not_intro (λ Ha : a, H ◂ Ha)
theorem heqt_elim {a : Bool} (H : a == true) : a
:= eqt_elim (to_eq H)
theorem not_true : (¬ true) = false
:= let aux : ¬ (¬ true) = true
:= assume H : (¬ true) = true,
absurd_not_true (subst trivial (symm H))
in resolve1 (boolcomplete (¬ true)) aux
theorem not_false : (¬ false) = true
:= let aux : ¬ (¬ false) = false
:= assume H : (¬ false) = false,
subst not_false_trivial H
in resolve1 (boolcomplete_swapped (¬ false)) aux
add_rewrite not_true not_false
theorem not_not_eq (a : Bool) : (¬ ¬ a) = a
:= case (λ x, (¬ ¬ x) = x)
(calc (¬ ¬ true) = (¬ false) : { not_true }
... = true : not_false)
(calc (¬ ¬ false) = (¬ true) : { not_false }
... = false : not_true)
a
add_rewrite not_not_eq
theorem not_neq {A : (Type U)} (a b : A) : ¬ (a ≠ b) ↔ a = b
:= not_not_eq (a = b)
add_rewrite not_neq
theorem not_neq_elim {A : (Type U)} {a b : A} (H : ¬ (a ≠ b)) : a = b
:= (not_neq a b) ◂ H
theorem not_not_elim {a : Bool} (H : ¬ ¬ a) : a
:= (not_not_eq a) ◂ H
theorem not_imp_eliml {a b : Bool} (Hnab : ¬ (a → b)) : a
:= not_not_elim
(show ¬ ¬ a,
from assume Hna : ¬ a, absurd (assume Ha : a, absurd_elim b Ha Hna)
Hnab)
theorem not_imp_elimr {a b : Bool} (H : ¬ (a → b)) : ¬ b
:= assume Hb : b, absurd (assume Ha : a, Hb)
H
-- Recall that and is defined as ¬ (a → ¬ b)
theorem and_intro {a b : Bool} (H1 : a) (H2 : b) : a ∧ b
:= assume H : a → ¬ b, absurd H2 (H H1)
theorem and_eliml {a b : Bool} (H : a ∧ b) : a
:= not_imp_eliml H
theorem and_elimr {a b : Bool} (H : a ∧ b) : b
:= not_not_elim (not_imp_elimr H)
theorem or_elim {a b c : Bool} (H1 : a b) (H2 : a → c) (H3 : b → c) : c
:= not_not_elim
(assume H : ¬ c,
absurd (H3 (resolve1 H1 (mt (assume Ha : a, H2 Ha) H)))
H)
theorem refute {a : Bool} (H : ¬ a → false) : a
:= or_elim (em a) (λ H1 : a, H1) (λ H1 : ¬ a, false_elim a (H H1))
theorem boolext {a b : Bool} (Hab : a → b) (Hba : b → a) : a = b
:= or_elim (boolcomplete a)
(λ Hat : a = true, or_elim (boolcomplete b)
(λ Hbt : b = true, trans Hat (symm Hbt))
(λ Hbf : b = false, false_elim (a = b) (subst (Hab (eqt_elim Hat)) Hbf)))
(λ Haf : a = false, or_elim (boolcomplete b)
(λ Hbt : b = true, false_elim (a = b) (subst (Hba (eqt_elim Hbt)) Haf))
(λ Hbf : b = false, trans Haf (symm Hbf)))
-- Another name for boolext
theorem iff_intro {a b : Bool} (Hab : a → b) (Hba : b → a) : a ↔ b
:= boolext Hab Hba
theorem eqt_intro {a : Bool} (H : a) : a = true
:= boolext (assume H1 : a, trivial)
(assume H2 : true, H)
theorem eqf_intro {a : Bool} (H : ¬ a) : a = false
:= boolext (assume H1 : a, absurd H1 H)
(assume H2 : false, false_elim a H2)
theorem a_neq_a {A : (Type U)} (a : A) : (a ≠ a) ↔ false
:= boolext (assume H, a_neq_a_elim H)
(assume H, false_elim (a ≠ a) H)
theorem eq_id {A : (Type U)} (a : A) : (a = a) ↔ true
:= eqt_intro (refl a)
theorem iff_id (a : Bool) : (a ↔ a) ↔ true
:= eqt_intro (refl a)
theorem heq_id (A : (Type U+1)) (a : A) : (a == a) ↔ true
:= eqt_intro (hrefl a)
theorem neq_elim {A : (Type U)} {a b : A} (H : a ≠ b) : a = b ↔ false
:= eqf_intro H
theorem neq_to_not_eq {A : (Type U)} {a b : A} : a ≠ b ↔ ¬ a = b
:= refl (a ≠ b)
add_rewrite eq_id iff_id neq_to_not_eq
-- Remark: ordered rewriting + assoc + comm + left_comm sorts a term lexicographically
theorem left_comm {A : (Type U)} {R : A -> A -> A} (comm : ∀ x y, R x y = R y x) (assoc : ∀ x y z, R (R x y) z = R x (R y z)) :
∀ x y z, R x (R y z) = R y (R x z)
:= take x y z, calc R x (R y z) = R (R x y) z : symm (assoc x y z)
... = R (R y x) z : { comm x y }
... = R y (R x z) : assoc y x z
theorem or_comm (a b : Bool) : (a b) = (b a)
:= boolext (assume H, or_elim H (λ H1, or_intror b H1) (λ H2, or_introl H2 a))
(assume H, or_elim H (λ H1, or_intror a H1) (λ H2, or_introl H2 b))
theorem or_assoc (a b c : Bool) : (a b) c ↔ a (b c)
:= boolext (assume H : (a b) c,
or_elim H (λ H1 : a b, or_elim H1 (λ Ha : a, or_introl Ha (b c))
(λ Hb : b, or_intror a (or_introl Hb c)))
(λ Hc : c, or_intror a (or_intror b Hc)))
(assume H : a (b c),
or_elim H (λ Ha : a, (or_introl (or_introl Ha b) c))
(λ H1 : b c, or_elim H1 (λ Hb : b, or_introl (or_intror a Hb) c)
(λ Hc : c, or_intror (a b) Hc)))
theorem or_id (a : Bool) : a a ↔ a
:= boolext (assume H, or_elim H (λ H1, H1) (λ H2, H2))
(assume H, or_introl H a)
theorem or_falsel (a : Bool) : a false ↔ a
:= boolext (assume H, or_elim H (λ H1, H1) (λ H2, false_elim a H2))
(assume H, or_introl H false)
theorem or_falser (a : Bool) : false a ↔ a
:= trans (or_comm false a) (or_falsel a)
theorem or_truel (a : Bool) : true a ↔ true
:= boolext (assume H : true a, trivial)
(assume H : true, or_introl trivial a)
theorem or_truer (a : Bool) : a true ↔ true
:= trans (or_comm a true) (or_truel a)
theorem or_tauto (a : Bool) : a ¬ a ↔ true
:= eqt_intro (em a)
theorem or_left_comm (a b c : Bool) : a (b c) ↔ b (a c)
:= left_comm or_comm or_assoc a b c
add_rewrite or_comm or_assoc or_id or_falsel or_falser or_truel or_truer or_tauto or_left_comm
theorem resolve2 {a b : Bool} (H1 : a b) (H2 : ¬ b) : a
:= resolve1 ((or_comm a b) ◂ H1) H2
theorem and_comm (a b : Bool) : a ∧ b ↔ b ∧ a
:= boolext (assume H, and_intro (and_elimr H) (and_eliml H))
(assume H, and_intro (and_elimr H) (and_eliml H))
theorem and_id (a : Bool) : a ∧ a ↔ a
:= boolext (assume H, and_eliml H)
(assume H, and_intro H H)
theorem and_assoc (a b c : Bool) : (a ∧ b) ∧ c ↔ a ∧ (b ∧ c)
:= boolext (assume H, and_intro (and_eliml (and_eliml H)) (and_intro (and_elimr (and_eliml H)) (and_elimr H)))
(assume H, and_intro (and_intro (and_eliml H) (and_eliml (and_elimr H))) (and_elimr (and_elimr H)))
theorem and_truer (a : Bool) : a ∧ true ↔ a
:= boolext (assume H : a ∧ true, and_eliml H)
(assume H : a, and_intro H trivial)
theorem and_truel (a : Bool) : true ∧ a ↔ a
:= trans (and_comm true a) (and_truer a)
theorem and_falsel (a : Bool) : a ∧ false ↔ false
:= boolext (assume H, and_elimr H)
(assume H, false_elim (a ∧ false) H)
theorem and_falser (a : Bool) : false ∧ a ↔ false
:= trans (and_comm false a) (and_falsel a)
theorem and_absurd (a : Bool) : a ∧ ¬ a ↔ false
:= boolext (assume H, absurd (and_eliml H) (and_elimr H))
(assume H, false_elim (a ∧ ¬ a) H)
theorem and_left_comm (a b c : Bool) : a ∧ (b ∧ c) ↔ b ∧ (a ∧ c)
:= left_comm and_comm and_assoc a b c
add_rewrite and_comm and_assoc and_id and_falsel and_falser and_truel and_truer and_absurd and_left_comm
theorem imp_truer (a : Bool) : (a → true) ↔ true
:= boolext (assume H, trivial)
(assume H Ha, trivial)
theorem imp_truel (a : Bool) : (true → a) ↔ a
:= boolext (assume H : true → a, H trivial)
(assume Ha H, Ha)
theorem imp_falser (a : Bool) : (a → false) ↔ ¬ a
:= refl _
theorem imp_falsel (a : Bool) : (false → a) ↔ true
:= boolext (assume H, trivial)
(assume H Hf, false_elim a Hf)
theorem imp_id (a : Bool) : (a → a) ↔ true
:= eqt_intro (λ H : a, H)
add_rewrite imp_truer imp_truel imp_falser imp_falsel imp_id
theorem imp_or (a b : Bool) : (a → b) ↔ ¬ a b
:= boolext
(assume H : a → b,
(or_elim (em a)
(λ Ha : a, or_intror (¬ a) (H Ha))
(λ Hna : ¬ a, or_introl Hna b)))
(assume H : ¬ a b,
assume Ha : a,
resolve1 H ((symm (not_not_eq a)) ◂ Ha))
theorem not_congr {a b : Bool} (H : a ↔ b) : ¬ a ↔ ¬ b
:= congr2 not H
-- Recall that exists is defined as ¬ ∀ x : A, ¬ P x
theorem exists_elim {A : (Type U)} {P : A → Bool} {B : Bool} (H1 : Exists A P) (H2 : ∀ (a : A) (H : P a), B) : B
:= refute (λ R : ¬ B,
absurd (take a : A, mt (assume H : P a, H2 a H) R)
H1)
theorem exists_intro {A : (Type U)} {P : A → Bool} (a : A) (H : P a) : Exists A P
:= assume H1 : (∀ x : A, ¬ P x),
absurd H (H1 a)
theorem not_exists (A : (Type U)) (P : A → Bool) : ¬ (∃ x : A, P x) ↔ (∀ x : A, ¬ P x)
:= calc (¬ ∃ x : A, P x) = ¬ ¬ ∀ x : A, ¬ P x : refl (¬ ∃ x : A, P x)
... = ∀ x : A, ¬ P x : not_not_eq (∀ x : A, ¬ P x)
theorem not_exists_elim {A : (Type U)} {P : A → Bool} (H : ¬ ∃ x : A, P x) : ∀ x : A, ¬ P x
:= (not_exists A P) ◂ H
theorem exists_unfold1 {A : (Type U)} {P : A → Bool} (a : A) (H : ∃ x : A, P x) : P a (∃ x : A, x ≠ a ∧ P x)
:= exists_elim H
(λ (w : A) (H1 : P w),
or_elim (em (w = a))
(λ Heq : w = a, or_introl (subst H1 Heq) (∃ x : A, x ≠ a ∧ P x))
(λ Hne : w ≠ a, or_intror (P a) (exists_intro w (and_intro Hne H1))))
theorem exists_unfold2 {A : (Type U)} {P : A → Bool} (a : A) (H : P a (∃ x : A, x ≠ a ∧ P x)) : ∃ x : A, P x
:= or_elim H
(λ H1 : P a, exists_intro a H1)
(λ H2 : (∃ x : A, x ≠ a ∧ P x),
exists_elim H2
(λ (w : A) (Hw : w ≠ a ∧ P w),
exists_intro w (and_elimr Hw)))
theorem exists_unfold {A : (Type U)} (P : A → Bool) (a : A) : (∃ x : A, P x) ↔ (P a (∃ x : A, x ≠ a ∧ P x))
:= boolext (assume H : (∃ x : A, P x), exists_unfold1 a H)
(assume H : (P a (∃ x : A, x ≠ a ∧ P x)), exists_unfold2 a H)
definition inhabited (A : (Type U))
:= ∃ x : A, true
-- If we have an element of type A, then A is inhabited
theorem inhabited_intro {A : (Type U)} (a : A) : inhabited A
:= assume H : (∀ x, ¬ true), absurd_not_true (H a)
theorem inhabited_elim {A : (Type U)} (H1 : inhabited A) {B : Bool} (H2 : A → B) : B
:= obtain (w : A) (Hw : true), from H1,
H2 w
theorem inhabited_ex_intro {A : (Type U)} {P : A → Bool} (H : ∃ x, P x) : inhabited A
:= obtain (w : A) (Hw : P w), from H,
exists_intro w trivial
-- If a function space is non-empty, then for every 'a' in the domain, the range (B a) is not empty
theorem inhabited_range {A : (Type U)} {B : A → (Type U)} (H : inhabited (∀ x, B x)) (a : A) : inhabited (B a)
:= refute (λ N : ¬ inhabited (B a),
let s1 : ¬ ∃ x : B a, true := N,
s2 : ∀ x : B a, false := take x : B a, absurd_not_true (not_exists_elim s1 x),
s3 : ∃ y : (∀ x, B x), true := H
in obtain (w : (∀ x, B x)) (Hw : true), from s3,
let s4 : B a := w a
in s2 s4)
theorem exists_rem {A : (Type U)} (H : inhabited A) (p : Bool) : (∃ x : A, p) ↔ p
:= iff_intro
(assume Hl : (∃ x : A, p),
obtain (w : A) (Hw : p), from Hl,
Hw)
(assume Hr : p,
inhabited_elim H (λ w, exists_intro w Hr))
theorem forall_rem {A : (Type U)} (H : inhabited A) (p : Bool) : (∀ x : A, p) ↔ p
:= iff_intro
(assume Hl : (∀ x : A, p),
inhabited_elim H (λ w, Hl w))
(assume Hr : p,
take x, Hr)
-- Congruence theorems for contextual simplification
-- Simplify a → b, by first simplifying a to c using the fact that ¬ b is true, and then
-- b to d using the fact that c is true
theorem imp_congrr {a b c d : Bool} (H_ac : ∀ (H_nb : ¬ b), a = c) (H_bd : ∀ (H_c : c), b = d) : (a → b) = (c → d)
:= or_elim (em b)
(λ H_b : b,
or_elim (em c)
(λ H_c : c,
calc (a → b) = (a → true) : { eqt_intro H_b }
... = true : imp_truer a
... = (c → true) : symm (imp_truer c)
... = (c → b) : { symm (eqt_intro H_b) }
... = (c → d) : { H_bd H_c })
(λ H_nc : ¬ c,
calc (a → b) = (a → true) : { eqt_intro H_b }
... = true : imp_truer a
... = (false → d) : symm (imp_falsel d)
... = (c → d) : { symm (eqf_intro H_nc) }))
(λ H_nb : ¬ b,
or_elim (em c)
(λ H_c : c,
calc (a → b) = (c → b) : { H_ac H_nb }
... = (c → d) : { H_bd H_c })
(λ H_nc : ¬ c,
calc (a → b) = (c → b) : { H_ac H_nb }
... = (false → b) : { eqf_intro H_nc }
... = true : imp_falsel b
... = (false → d) : symm (imp_falsel d)
... = (c → d) : { symm (eqf_intro H_nc) }))
-- Simplify a → b, by first simplifying b to d using the fact that a is true, and then
-- b to d using the fact that ¬ d is true.
-- This kind of congruence seems to be useful in very rare cases.
theorem imp_congrl {a b c d : Bool} (H_bd : ∀ (H_a : a), b = d) (H_ac : ∀ (H_nd : ¬ d), a = c) : (a → b) = (c → d)
:= or_elim (em a)
(λ H_a : a,
or_elim (em d)
(λ H_d : d,
calc (a → b) = (a → d) : { H_bd H_a }
... = (a → true) : { eqt_intro H_d }
... = true : imp_truer a
... = (c → true) : symm (imp_truer c)
... = (c → d) : { symm (eqt_intro H_d) })
(λ H_nd : ¬ d,
calc (a → b) = (c → b) : { H_ac H_nd }
... = (c → d) : { H_bd H_a }))
(λ H_na : ¬ a,
or_elim (em d)
(λ H_d : d,
calc (a → b) = (false → b) : { eqf_intro H_na }
... = true : imp_falsel b
... = (c → true) : symm (imp_truer c)
... = (c → d) : { symm (eqt_intro H_d) })
(λ H_nd : ¬ d,
calc (a → b) = (false → b) : { eqf_intro H_na }
... = true : imp_falsel b
... = (false → d) : symm (imp_falsel d)
... = (a → d) : { symm (eqf_intro H_na) }
... = (c → d) : { H_ac H_nd }))
-- (Common case) simplify a to c, and then b to d using the fact that c is true
theorem imp_congr {a b c d : Bool} (H_ac : a = c) (H_bd : ∀ (H_c : c), b = d) : (a → b) = (c → d)
:= imp_congrr (λ H, H_ac) H_bd
-- In the following theorems we are using the fact that a b is defined as ¬ a → b
theorem or_congrr {a b c d : Bool} (H_ac : ∀ (H_nb : ¬ b), a = c) (H_bd : ∀ (H_nc : ¬ c), b = d) : a b ↔ c d
:= imp_congrr (λ H_nb : ¬ b, congr2 not (H_ac H_nb)) H_bd
theorem or_congrl {a b c d : Bool} (H_bd : ∀ (H_na : ¬ a), b = d) (H_ac : ∀ (H_nd : ¬ d), a = c) : a b ↔ c d
:= imp_congrl H_bd (λ H_nd : ¬ d, congr2 not (H_ac H_nd))
-- (Common case) simplify a to c, and then b to d using the fact that ¬ c is true
theorem or_congr {a b c d : Bool} (H_ac : a = c) (H_bd : ∀ (H_nc : ¬ c), b = d) : a b ↔ c d
:= or_congrr (λ H, H_ac) H_bd
-- In the following theorems we are using the fact hat a ∧ b is defined as ¬ (a → ¬ b)
theorem and_congrr {a b c d : Bool} (H_ac : ∀ (H_b : b), a = c) (H_bd : ∀ (H_c : c), b = d) : a ∧ b ↔ c ∧ d
:= congr2 not (imp_congrr (λ (H_nnb : ¬ ¬ b), H_ac (not_not_elim H_nnb)) (λ H_c : c, congr2 not (H_bd H_c)))
theorem and_congrl {a b c d : Bool} (H_bd : ∀ (H_a : a), b = d) (H_ac : ∀ (H_d : d), a = c) : a ∧ b ↔ c ∧ d
:= congr2 not (imp_congrl (λ H_a : a, congr2 not (H_bd H_a)) (λ (H_nnd : ¬ ¬ d), H_ac (not_not_elim H_nnd)))
-- (Common case) simplify a to c, and then b to d using the fact that c is true
theorem and_congr {a b c d : Bool} (H_ac : a = c) (H_bd : ∀ (H_c : c), b = d) : a ∧ b ↔ c ∧ d
:= and_congrr (λ H, H_ac) H_bd
theorem not_and (a b : Bool) : ¬ (a ∧ b) ↔ ¬ a ¬ b
:= boolext (assume H, or_elim (em a)
(assume Ha, or_elim (em b)
(assume Hb, absurd_elim (¬ a ¬ b) (and_intro Ha Hb) H)
(assume Hnb, or_intror (¬ a) Hnb))
(assume Hna, or_introl Hna (¬ b)))
(assume (H : ¬ a ¬ b) (N : a ∧ b),
or_elim H
(assume Hna, absurd (and_eliml N) Hna)
(assume Hnb, absurd (and_elimr N) Hnb))
theorem not_and_elim {a b : Bool} (H : ¬ (a ∧ b)) : ¬ a ¬ b
:= (not_and a b) ◂ H
theorem not_or (a b : Bool) : ¬ (a b) ↔ ¬ a ∧ ¬ b
:= boolext (assume H, or_elim (em a)
(assume Ha, absurd_elim (¬ a ∧ ¬ b) (or_introl Ha b) H)
(assume Hna, or_elim (em b)
(assume Hb, absurd_elim (¬ a ∧ ¬ b) (or_intror a Hb) H)
(assume Hnb, and_intro Hna Hnb)))
(assume (H : ¬ a ∧ ¬ b) (N : a b),
or_elim N
(assume Ha, absurd Ha (and_eliml H))
(assume Hb, absurd Hb (and_elimr H)))
theorem not_or_elim {a b : Bool} (H : ¬ (a b)) : ¬ a ∧ ¬ b
:= (not_or a b) ◂ H
theorem not_implies (a b : Bool) : ¬ (a → b) ↔ a ∧ ¬ b
:= calc (¬ (a → b)) = ¬ (¬ a b) : { imp_or a b }
... = ¬ ¬ a ∧ ¬ b : not_or (¬ a) b
... = a ∧ ¬ b : by simp
theorem not_implies_elim {a b : Bool} (H : ¬ (a → b)) : a ∧ ¬ b
:= (not_implies a b) ◂ H
theorem a_eq_not_a (a : Bool) : (a = ¬ a) ↔ false
:= boolext (λ H, or_elim (em a)
(λ Ha, absurd Ha (subst Ha H))
(λ Hna, absurd (subst Hna (symm H)) Hna))
(λ H, false_elim (a = ¬ a) H)
theorem a_iff_not_a (a : Bool) : (a ↔ ¬ a) ↔ false
:= a_eq_not_a a
theorem true_eq_false : (true = false) ↔ false
:= subst (a_eq_not_a true) not_true
theorem true_iff_false : (true ↔ false) ↔ false
:= true_eq_false
theorem false_eq_true : (false = true) ↔ false
:= subst (a_eq_not_a false) not_false
theorem false_iff_true : (false ↔ true) ↔ false
:= false_eq_true
theorem a_iff_true (a : Bool) : (a ↔ true) ↔ a
:= boolext (λ H, eqt_elim H)
(λ H, eqt_intro H)
theorem a_iff_false (a : Bool) : (a ↔ false) ↔ ¬ a
:= boolext (λ H, eqf_elim H)
(λ H, eqf_intro H)
add_rewrite a_eq_not_a a_iff_not_a true_eq_false true_iff_false false_eq_true false_iff_true a_iff_true a_iff_false
theorem not_iff (a b : Bool) : ¬ (a ↔ b) ↔ (¬ a ↔ b)
:= or_elim (em b)
(λ Hb, calc (¬ (a ↔ b)) = (¬ (a ↔ true)) : { eqt_intro Hb }
... = ¬ a : { a_iff_true a }
... = ¬ a ↔ true : { symm (a_iff_true (¬ a)) }
... = ¬ a ↔ b : { symm (eqt_intro Hb) })
(λ Hnb, calc (¬ (a ↔ b)) = (¬ (a ↔ false)) : { eqf_intro Hnb }
... = ¬ ¬ a : { a_iff_false a }
... = ¬ a ↔ false : { symm (a_iff_false (¬ a)) }
... = ¬ a ↔ b : { symm (eqf_intro Hnb) })
theorem not_iff_elim {a b : Bool} (H : ¬ (a ↔ b)) : (¬ a) ↔ b
:= (not_iff a b) ◂ H
theorem forall_or_distributer {A : (Type U)} (p : Bool) (φ : A → Bool) : (∀ x, p φ x) = (p ∀ x, φ x)
:= boolext
(assume H : (∀ x, p φ x),
or_elim (em p)
(λ Hp : p, or_introl Hp (∀ x, φ x))
(λ Hnp : ¬ p, or_intror p (take x,
resolve1 (H x) Hnp)))
(assume H : (p ∀ x, φ x),
take x,
or_elim H
(λ H1 : p, or_introl H1 (φ x))
(λ H2 : (∀ x, φ x), or_intror p (H2 x)))
theorem forall_or_distributel {A : Type} (p : Bool) (φ : A → Bool) : (∀ x, φ x p) = ((∀ x, φ x) p)
:= boolext
(assume H : (∀ x, φ x p),
or_elim (em p)
(λ Hp : p, or_intror (∀ x, φ x) Hp)
(λ Hnp : ¬ p, or_introl (take x, resolve2 (H x) Hnp) p))
(assume H : (∀ x, φ x) p,
take x,
or_elim H
(λ H1 : (∀ x, φ x), or_introl (H1 x) p)
(λ H2 : p, or_intror (φ x) H2))
theorem forall_and_distribute {A : (Type U)} (φ ψ : A → Bool) : (∀ x, φ x ∧ ψ x) ↔ (∀ x, φ x) ∧ (∀ x, ψ x)
:= boolext
(assume H : (∀ x, φ x ∧ ψ x),
and_intro (take x, and_eliml (H x)) (take x, and_elimr (H x)))
(assume H : (∀ x, φ x) ∧ (∀ x, ψ x),
take x, and_intro (and_eliml H x) (and_elimr H x))
theorem exists_and_distributer {A : (Type U)} (p : Bool) (φ : A → Bool) : (∃ x, p ∧ φ x) ↔ p ∧ ∃ x, φ x
:= boolext
(assume H : (∃ x, p ∧ φ x),
obtain (w : A) (Hw : p ∧ φ w), from H,
and_intro (and_eliml Hw) (exists_intro w (and_elimr Hw)))
(assume H : (p ∧ ∃ x, φ x),
obtain (w : A) (Hw : φ w), from (and_elimr H),
exists_intro w (and_intro (and_eliml H) Hw))
theorem exists_or_distribute {A : (Type U)} (φ ψ : A → Bool) : (∃ x, φ x ψ x) ↔ (∃ x, φ x) (∃ x, ψ x)
:= boolext
(assume H : (∃ x, φ x ψ x),
obtain (w : A) (Hw : φ w ψ w), from H,
or_elim Hw
(λ Hw1 : φ w, or_introl (exists_intro w Hw1) (∃ x, ψ x))
(λ Hw2 : ψ w, or_intror (∃ x, φ x) (exists_intro w Hw2)))
(assume H : (∃ x, φ x) (∃ x, ψ x),
or_elim H
(λ H1 : (∃ x, φ x),
obtain (w : A) (Hw : φ w), from H1,
exists_intro w (or_introl Hw (ψ w)))
(λ H2 : (∃ x, ψ x),
obtain (w : A) (Hw : ψ w), from H2,
exists_intro w (or_intror (φ w) Hw)))
theorem eq_exists_intro {A : (Type U)} {P Q : A → Bool} (H : ∀ x : A, P x ↔ Q x) : (∃ x : A, P x) ↔ (∃ x : A, Q x)
:= boolext
(assume Hex, obtain w Pw, from Hex, exists_intro w ((H w) ◂ Pw))
(assume Hex, obtain w Qw, from Hex, exists_intro w ((symm (H w)) ◂ Qw))
theorem not_forall (A : (Type U)) (P : A → Bool) : ¬ (∀ x : A, P x) ↔ (∃ x : A, ¬ P x)
:= boolext
(assume H, refute (λ N : ¬ (∃ x, ¬ P x),
absurd (take x, not_not_elim (not_exists_elim N x)) H))
(assume (H : ∃ x, ¬ P x) (N : ∀ x, P x),
obtain w Hw, from H,
absurd (N w) Hw)
theorem not_forall_elim {A : (Type U)} {P : A → Bool} (H : ¬ (∀ x : A, P x)) : ∃ x : A, ¬ P x
:= (not_forall A P) ◂ H
theorem exists_and_distributel {A : (Type U)} (p : Bool) (φ : A → Bool) : (∃ x, φ x ∧ p) ↔ (∃ x, φ x) ∧ p
:= calc (∃ x, φ x ∧ p) = (∃ x, p ∧ φ x) : eq_exists_intro (λ x, and_comm (φ x) p)
... = (p ∧ (∃ x, φ x)) : exists_and_distributer p φ
... = ((∃ x, φ x) ∧ p) : and_comm p (∃ x, φ x)
theorem exists_imp_distribute {A : (Type U)} (φ ψ : A → Bool) : (∃ x, φ x → ψ x) ↔ ((∀ x, φ x) → (∃ x, ψ x))
:= calc (∃ x, φ x → ψ x) = (∃ x, ¬ φ x ψ x) : eq_exists_intro (λ x, imp_or (φ x) (ψ x))
... = (∃ x, ¬ φ x) (∃ x, ψ x) : exists_or_distribute _ _
... = ¬ (∀ x, φ x) (∃ x, ψ x) : { symm (not_forall A φ) }
... = (∀ x, φ x) → (∃ x, ψ x) : symm (imp_or _ _)
theorem forall_uninhabited {A : (Type U)} {B : A → Bool} (H : ¬ inhabited A) : ∀ x, B x
:= refute (λ N : ¬ (∀ x, B x),
obtain w Hw, from not_forall_elim N,
absurd (inhabited_intro w) H)
theorem allext {A : (Type U)} {B C : A → Bool} (H : ∀ x : A, B x = C x) : (∀ x : A, B x) = (∀ x : A, C x)
:= boolext
(assume Hl, take x, (H x) ◂ (Hl x))
(assume Hr, take x, (symm (H x)) ◂ (Hr x))
theorem proj1_congr {A : (Type U)} {B : A → (Type U)} {a b : sig x, B x} (H : a = b) : proj1 a = proj1 b
:= subst (refl (proj1 a)) H
theorem proj2_congr {A B : (Type U)} {a b : A # B} (H : a = b) : proj2 a = proj2 b
:= subst (refl (proj2 a)) H
theorem hproj2_congr {A : (Type U)} {B : A → (Type U)} {a b : sig x, B x} (H : a = b) : proj2 a == proj2 b
:= subst (hrefl (proj2 a)) H
definition pair {A : (Type U)} {B : A → (Type U)} (a : A) (b : B a) := tuple (sig x : A, B x) : a, b
-- Up to this point, we proved all theorems using just reflexivity, substitution and case (proof by cases)
-- Function extensionality
axiom funext {A : (Type U)} {B : A → (Type U)} {f g : ∀ x : A, B x} (H : ∀ x : A, f x = g x) : f = g
-- Eta is a consequence of function extensionality
theorem eta {A : (Type U)} {B : A → (Type U)} (f : ∀ x : A, B x) : (λ x : A, f x) = f
:= funext (λ x : A, refl (f x))
-- Epsilon (Hilbert's operator)
variable eps {A : (Type U)} (H : inhabited A) (P : A → Bool) : A
alias ε : eps
axiom eps_ax {A : (Type U)} (H : inhabited A) {P : A → Bool} (a : A) : P a → P (ε H P)
theorem eps_th {A : (Type U)} {P : A → Bool} (a : A) : P a → P (ε (inhabited_intro a) P)
:= assume H : P a, @eps_ax A (inhabited_intro a) P a H
theorem eps_singleton {A : (Type U)} (H : inhabited A) (a : A) : ε H (λ x, x = a) = a
:= let P := λ x, x = a,
Ha : P a := refl a
in eps_ax H a Ha
-- A function space (∀ x : A, B x) is inhabited if forall a : A, we have inhabited (B a)
theorem inhabited_dfun {A : (Type U)} {B : A → (Type U)} (Hn : ∀ a, inhabited (B a)) : inhabited (∀ x, B x)
:= inhabited_intro (λ x, ε (Hn x) (λ y, true))
theorem inhabited_fun (A : (Type U)) {B : (Type U)} (H : inhabited B) : inhabited (A → B)
:= inhabited_intro (λ x, ε H (λ y, true))
theorem exists_to_eps {A : (Type U)} {P : A → Bool} (H : ∃ x, P x) : P (ε (inhabited_ex_intro H) P)
:= obtain (w : A) (Hw : P w), from H,
eps_ax (inhabited_ex_intro H) w Hw
theorem axiom_of_choice {A : (Type U)} {B : A → (Type U)} {R : ∀ x : A, B x → Bool} (H : ∀ x, ∃ y, R x y) : ∃ f, ∀ x, R x (f x)
:= exists_intro
(λ x, ε (inhabited_ex_intro (H x)) (λ y, R x y)) -- witness for f
(λ x, exists_to_eps (H x)) -- proof that witness satisfies ∀ x, R x (f x)
theorem skolem_th {A : (Type U)} {B : A → (Type U)} {P : ∀ x : A, B x → Bool} :
(∀ x, ∃ y, P x y) ↔ ∃ f, (∀ x, P x (f x))
:= iff_intro
(λ H : (∀ x, ∃ y, P x y), axiom_of_choice H)
(λ H : (∃ f, (∀ x, P x (f x))),
take x, obtain (fw : ∀ x, B x) (Hw : ∀ x, P x (fw x)), from H,
exists_intro (fw x) (Hw x))
-- if-then-else expression, we define it using Hilbert's operator
definition ite {A : (Type U)} (c : Bool) (a b : A) : A
:= ε (inhabited_intro a) (λ r, (c → r = a) ∧ (¬ c → r = b))
notation 45 if _ then _ else _ : ite
theorem if_true {A : (Type U)} (a b : A) : (if true then a else b) = a
:= calc (if true then a else b) = ε (inhabited_intro a) (λ r, (true → r = a) ∧ (¬ true → r = b)) : refl (if true then a else b)
... = ε (inhabited_intro a) (λ r, r = a) : by simp
... = a : eps_singleton (inhabited_intro a) a
theorem if_false {A : (Type U)} (a b : A) : (if false then a else b) = b
:= calc (if false then a else b) = ε (inhabited_intro a) (λ r, (false → r = a) ∧ (¬ false → r = b)) : refl (if false then a else b)
... = ε (inhabited_intro a) (λ r, r = b) : by simp
... = b : eps_singleton (inhabited_intro a) b
theorem if_a_a {A : (Type U)} (c : Bool) (a: A) : (if c then a else a) = a
:= or_elim (em c)
(λ H : c, calc (if c then a else a) = (if true then a else a) : { eqt_intro H }
... = a : if_true a a)
(λ H : ¬ c, calc (if c then a else a) = (if false then a else a) : { eqf_intro H }
... = a : if_false a a)
add_rewrite if_true if_false if_a_a
theorem if_congr {A : (Type U)} {b c : Bool} {x y u v : A} (H_bc : b = c)
(H_xu : ∀ (H_c : c), x = u) (H_yv : ∀ (H_nc : ¬ c), y = v) :
(if b then x else y) = if c then u else v
:= or_elim (em c)
(λ H_c : c, calc
(if b then x else y) = if c then x else y : { H_bc }
... = if true then x else y : { eqt_intro H_c }
... = x : if_true _ _
... = u : H_xu H_c
... = if true then u else v : symm (if_true _ _)
... = if c then u else v : { symm (eqt_intro H_c) })
(λ H_nc : ¬ c, calc
(if b then x else y) = if c then x else y : { H_bc }
... = if false then x else y : { eqf_intro H_nc }
... = y : if_false _ _
... = v : H_yv H_nc
... = if false then u else v : symm (if_false _ _)
... = if c then u else v : { symm (eqf_intro H_nc) })
theorem if_imp_then {a b c : Bool} (H : if a then b else c) : a → b
:= assume Ha : a, eqt_elim (calc b = if true then b else c : symm (if_true b c)
... = if a then b else c : { symm (eqt_intro Ha) }
... = true : eqt_intro H)
theorem if_imp_else {a b c : Bool} (H : if a then b else c) : ¬ a → c
:= assume Hna : ¬ a, eqt_elim (calc c = if false then b else c : symm (if_false b c)
... = if a then b else c : { symm (eqf_intro Hna) }
... = true : eqt_intro H)
theorem app_if_distribute {A B : (Type U)} (c : Bool) (f : A → B) (a b : A) : f (if c then a else b) = if c then f a else f b
:= or_elim (em c)
(λ Hc : c , calc
f (if c then a else b) = f (if true then a else b) : { eqt_intro Hc }
... = f a : { if_true a b }
... = if true then f a else f b : symm (if_true (f a) (f b))
... = if c then f a else f b : { symm (eqt_intro Hc) })
(λ Hnc : ¬ c, calc
f (if c then a else b) = f (if false then a else b) : { eqf_intro Hnc }
... = f b : { if_false a b }
... = if false then f a else f b : symm (if_false (f a) (f b))
... = if c then f a else f b : { symm (eqf_intro Hnc) })
theorem eq_if_distributer {A : (Type U)} (c : Bool) (a b v : A) : (v = (if c then a else b)) = if c then v = a else v = b
:= app_if_distribute c (eq v) a b
theorem eq_if_distributel {A : (Type U)} (c : Bool) (a b v : A) : ((if c then a else b) = v) = if c then a = v else b = v
:= app_if_distribute c (λ x, x = v) a b
set_opaque exists true
set_opaque not true
set_opaque or true
set_opaque and true
set_opaque implies true
set_opaque ite true
set_opaque eq true
definition injective {A B : (Type U)} (f : A → B) := ∀ x1 x2, f x1 = f x2 → x1 = x2
definition non_surjective {A B : (Type U)} (f : A → B) := ∃ y, ∀ x, ¬ f x = y
-- The set of individuals, we need to assert the existence of one infinite set
variable ind : Type
-- ind is infinite, i.e., there is a function f s.t. f is injective, and not surjective
axiom infinity : ∃ f : ind → ind, injective f ∧ non_surjective f
-- Pair extensionality
axiom pairext {A : (Type U)} {B : A → (Type U)} (a b : sig x, B x)
(H1 : proj1 a = proj1 b) (H2 : proj2 a == proj2 b)
: a = b
theorem pair_proj_eq {A : (Type U)} {B : A → (Type U)} (a : sig x, B x) : pair (proj1 a) (proj2 a) = a
:= have Heq1 : proj1 (pair (proj1 a) (proj2 a)) = proj1 a,
from refl (proj1 a),
have Heq2 : proj2 (pair (proj1 a) (proj2 a)) == proj2 a,
from hrefl (proj2 a),
show pair (proj1 a) (proj2 a) = a,
from pairext (pair (proj1 a) (proj2 a)) a Heq1 Heq2
theorem pair_congr {A : (Type U)} {B : A → (Type U)} {a a' : A} {b : B a} {b' : B a'} (Ha : a = a') (Hb : b == b')
: (pair a b) = (pair a' b')
:= have Heq1 : proj1 (pair a b) = proj1 (pair a' b'),
from Ha,
have Heq2 : proj2 (pair a b) == proj2 (pair a' b'),
from Hb,
show (pair a b) = (pair a' b'),
from pairext (pair a b) (pair a' b') Heq1 Heq2
theorem pairext_proj {A B : (Type U)} {p : A # B} {a : A} {b : B} (H1 : proj1 p = a) (H2 : proj2 p = b) : p = (pair a b)
:= pairext p (pair a b) H1 (to_heq H2)
theorem hpairext_proj {A : (Type U)} {B : A → (Type U)} {p : sig x, B x} {a : A} {b : B a}
(H1 : proj1 p = a) (H2 : proj2 p == b) : p = (pair a b)
:= pairext p (pair a b) H1 H2
-- Heterogeneous equality axioms and theorems
-- We can "type-cast" an A expression into a B expression, if we can prove that A == B
-- Remark: we use A == B instead of A = B, because A = B would be type incorrect.
-- A = B is actually (@eq (Type U) A B), which is type incorrect because
-- the first argument of eq must have type (Type U) and the type of (Type U) is (Type U+1)
variable cast {A B : (Type U+1)} : A == B → A → B
axiom cast_heq {A B : (Type U+1)} (H : A == B) (a : A) : cast H a == a
-- Heterogeneous equality satisfies the usual properties: symmetry, transitivity, congruence, function extensionality, ...
-- Heterogeneous version of subst
axiom hsubst {A B : (Type U+1)} {a : A} {b : B} (P : ∀ T : (Type U+1), T → Bool) : P A a → a == b → P B b
theorem hsymm {A B : (Type U+1)} {a : A} {b : B} (H : a == b) : b == a
:= hsubst (λ (T : (Type U+1)) (x : T), x == a) (hrefl a) H
theorem htrans {A B C : (Type U+1)} {a : A} {b : B} {c : C} (H1 : a == b) (H2 : b == c) : a == c
:= hsubst (λ (T : (Type U+1)) (x : T), a == x) H1 H2
axiom hcongr {A A' : (Type U+1)} {B : A → (Type U+1)} {B' : A' → (Type U+1)} {f : ∀ x, B x} {f' : ∀ x, B' x} {a : A} {a' : A'} :
f == f' → a == a' → f a == f' a'
axiom hfunext {A A' : (Type U+1)} {B : A → (Type U+1)} {B' : A' → (Type U+1)} {f : ∀ x, B x} {f' : ∀ x, B' x} :
A == A' → (∀ x x', x == x' → f x == f' x') → f == f'
axiom hpiext {A A' : (Type U+1)} {B : A → (Type U+1)} {B' : A' → (Type U+1)} :
A == A' → (∀ x x', x == x' → B x == B' x') → (∀ x, B x) == (∀ x, B' x)
axiom hsigext {A A' : (Type U+1)} {B : A → (Type U+1)} {B' : A' → (Type U+1)} :
A == A' → (∀ x x', x == x' → B x == B' x') → (sig x, B x) == (sig x, B' x)
-- Heterogeneous version of the allext theorem
theorem hallext {A A' : (Type U+1)} {B : A → Bool} {B' : A' → Bool}
(Ha : A == A') (Hb : ∀ x x', x == x' → B x = B' x') : (∀ x, B x) = (∀ x, B' x)
:= to_eq (hpiext Ha (λ x x' Heq, to_heq (Hb x x' Heq)))
-- Simpler version of hfunext axiom, we use it to build proofs
theorem hsfunext {A : (Type U)} {B B' : A → (Type U)} {f : ∀ x, B x} {f' : ∀ x, B' x} :
(∀ x, f x == f' x) → f == f'
:= λ Hb,
hfunext (hrefl A) (λ (x x' : A) (Heq : x == x'),
let s1 : f x == f' x := Hb x,
s2 : f' x == f' x' := hcongr (hrefl f') Heq
in htrans s1 s2)
theorem heq_congr {A B : (Type U)} {a a' : A} {b b' : B} (H1 : a = a') (H2 : b = b') : (a == b) = (a' == b')
:= calc (a == b) = (a' == b) : { H1 }
... = (a' == b') : { H2 }
theorem hheq_congr {A A' B B' : (Type U+1)} {a : A} {a' : A'} {b : B} {b' : B'} (H1 : a == a') (H2 : b == b') : (a == b) = (a' == b')
:= have Heq1 : (a == b) = (a' == b),
from (hsubst (λ (T : (Type U+1)) (x : T), (a == b) = (x == b)) (refl (a == b)) H1),
have Heq2 : (a' == b) = (a' == b'),
from (hsubst (λ (T : (Type U+1)) (x : T), (a' == b) = (a' == x)) (refl (a' == b)) H2),
show (a == b) = (a' == b'),
from trans Heq1 Heq2
theorem type_eq {A B : (Type U)} {a : A} {b : B} (H : a == b) : A == B
:= hsubst (λ (T : (Type U+1)) (x : T), A == T) (hrefl A) H
-- Some theorems that are useful for applying simplifications.
theorem cast_eq {A : (Type U)} (H : A == A) (a : A) : cast H a = a
:= to_eq (cast_heq H a)
theorem cast_trans {A B C : (Type U)} (Hab : A == B) (Hbc : B == C) (a : A) : cast Hbc (cast Hab a) = cast (htrans Hab Hbc) a
:= have Heq1 : cast Hbc (cast Hab a) == cast Hab a,
from cast_heq Hbc (cast Hab a),
have Heq2 : cast Hab a == a,
from cast_heq Hab a,
have Heq3 : cast (htrans Hab Hbc) a == a,
from cast_heq (htrans Hab Hbc) a,
show cast Hbc (cast Hab a) = cast (htrans Hab Hbc) a,
from to_eq (htrans (htrans Heq1 Heq2) (hsymm Heq3))
theorem cast_pull {A : (Type U)} {B B' : A → (Type U)}
(f : ∀ x, B x) (a : A) (Hb : (∀ x, B x) == (∀ x, B' x)) (Hba : (B a) == (B' a)) :
cast Hb f a = cast Hba (f a)
:= have s1 : cast Hb f a == f a,
from hcongr (cast_heq Hb f) (hrefl a),
have s2 : cast Hba (f a) == f a,
from cast_heq Hba (f a),
show cast Hb f a = cast Hba (f a),
from to_eq (htrans s1 (hsymm s2))
-- Proof irrelevance is true in the set theoretic model we have for Lean.
axiom proof_irrel {a : Bool} (H1 H2 : a) : H1 = H2
-- A more general version of proof_irrel that can be be derived using proof_irrel, heq axioms and boolext/iff_intro
theorem hproof_irrel {a b : Bool} (H1 : a) (H2 : b) : H1 == H2
:= let Hab : a == b := to_heq (iff_intro (assume Ha, H2) (assume Hb, H1)),
H1b : b := cast Hab H1,
H1_eq_H1b : H1 == H1b := hsymm (cast_heq Hab H1),
H1b_eq_H2 : H1b == H2 := to_heq (proof_irrel H1b H2)
in htrans H1_eq_H1b H1b_eq_H2